Consensus statements for pharmacological management, monitoring of therapies, and comorbidity management of psoriatic arthritis in the United Arab Emirates. (2nd August 2022) - Alnaqbi, Khalid A.; Hannawi, Suad; Namas, Rajaie; Alshehhi, Waleed; Badsha, Humeira; Al‐Saleh, Jamal
Abstract: Objective: Psoriatic arthritis (PsA), a chronic inflammatory disease characterized by heterogeneous clinical manifestations, substantially impacts the quality of life of affected individuals. This article aims at developing consensus recommendations for the management of PsA and associated comorbidities and screening and monitoring requirements of PsA therapies in the United Arab Emirates (UAE) population. Methods: An extensive review of present international and regional guidelines and publications on the pharmacological management, monitoring of therapies in the context of PsA was performed. Key findings from guidelines and literature were reviewed by a panel of experts from the UAE at several meetings to align with current clinical practices. Consensus statements were formulated based on collective agreement of the experts and members of Emirates Society for Rheumatology. Results: The consensus recommendations were developed to aid practitioners in clinical decision‐making with respect to dosage recommendations for pharmacological therapies for PsA, including conventional drugs, non‐biologic, and biologic therapies. Consensus recommendations for therapeutic options for the treatment of PsA domains, including peripheral arthritis, axial disease, enthesitis, dactylitis, psoriasis, and nail disease, were developed. The panel emphasized the importance of monitoring PsA therapies and arrived at a consensus on monitoring requirements for PsA therapies. The expert panel proposed recommendations for the management of common comorbidities associated with PsA. Conclusion: These consensus recommendations can guide physicians and healthcare professionals in the UAE in making proper treatment decisions, as well as efficiently managing comorbidities and monitoring therapies in patients with PsA.